Fsc Part 1 Mathematics (Complete Solution)

Q5
Simplify by expressing in the form a+bι

(i) 5 + 2 -4 

SOLUTION:

5+2 -4  =5+2 (-1)(4) 

= 5+2(√ )( -1 )

=5+2[(2)(ι)]                                                            [ ∴ ι= -1  ]

=5+2(2ι)

=5+4ι   

(ii) (2+( -3 )(3+( -3 )

SOLUTION:

(2+( -3 )(3+( -3 )=[2+( (-1)(3) ][3+( (-1)(3) ]

=[2+( 3  )(√ -1 )][3+( 3 )( -1 )]

=[2+( 3  )(ι)][3+( 3  )(ι)]                                [ ∴ ι= -1  ]

=(2+ 3  ι)(3+ 3  ι)

=(2)(3)+(2)( 3  ι)+(√ 3  ι)(3)+( 3  ι)(√ 3  ι)

=6+2 3  ι+3 3  ι+3 ι2

=6+5 3  ι+3(-1)                                               [ ∴  ι2=-1]                          

=6-3+5 3  ι

=3+5 3  ι

(iii)
2
 5 + -8 

SOLUTION:
2
 5  + -8 

=
2
 5  + (-1)(8) 

=
2
 5  +2√  ι
 

[ ∴ ι= -1  ]

=
2
 5  +2√  ι
x
 5  -2√  ι
 5  -2√  ι

=
2(  5  -2√  ι)
(√  5  +2√  ι)(  5  -2√  ι)

=
2  5  -4  ι
(  5  )2-(2√  ι)2

=
2  5  -4  ι
5 - (4)(2) ι2

=
2  5  -4  ι
5 - 8(-1)

=
2(√  5  -2  ι)
13

=
2  5  
13
-
4  ι
13

(iv)
3
 6   -   -12  

SOLUTION:
3
 6  + -12 

=
3
 6  + (-1)(12) 

=
3
 6 +[√ -1  ][  12 ]

   [ ∴ ι= -1  ]

=
3
 6  +  12 ι

=
3
 6  +  12 ι
x
 6  -√ 12 ι
 6  -√  12 ι

=
3(  6  -√  12 ι)
(√  6  +  12 ι)(  6  -√ 12 ι)

=
3(  6  -√  12ι)
(√  6  )2-(√  12 ι)2

=
3(√  6  -√  12 ι)
6-12ι2

=
3(  6  -√  12 ι)
6-12(-1)

=
3(  6  -√  12 ι)
18

=
1(  6  -√  12 ι)
6

=
 6  
6
-
 12 ι
6

=
 6  
(  6  )(  6  )
-
( 6 )( 2  )ι
 (  6  )(  2  )(  3  )

=
1
 6  
-
ι
   3  

Other Topics

;